An analysis of crime pattern using [GIS] approach / Hamisah Haiyaton Md Sakili - Md Sakili, Hamisah Haiyaton (2019)
Crime is act harmful not only to some individual but also to community, society or state. The fear on crime and insecurity are the reality in life oppose. This paper research indicates the relationship of criminal activities with land use and their implications on the society at both the relative. The aim of this study is to review spatial analysis of crime pattern at Montgomery county Maryland on year 2016 and 2017. There are four type of crime has been classified based on the crime cases reported on year 2016 and 2017. By using GIS (Geographical Information System), spatial analyst tools with density method and spatial statistic tool with hotspot is performed in order to determine the crime pattern. The study then produces the map distribution of crime on year 2016 and 2017. Besides that, the hotspot and kernel density estimation map to determine the crime pattern. The overall finding from this research that there have large changes on the crime pattern between year 2016 and 2017. For the both method of hotspot and kernel density estimation is the best method used to identify and determine the crime pattern in Montgomery and also for the general understanding on crime pattern.. In conclusion, this research paper suggests that the application and integration of GIS techniques could assist the law enforcement in monitoring potential crime location and improvement in internal management of information in wide use of geographic information system (GIS).